Guided Inquiry Learning Model to Improve Scientific Literacy on Energy and Its Transformation - Tanti Sugiharti; Arvy Noleal Osma (International Journal of Science and Mathematics Education, 2024)
This study investigates the effectiveness of the Guided Inquiry Learning (GIL) model in enhancing students' scientific literacy, particularly in the domain of energy and its transformation. The primary aim of the research was to assess the impact of GIL on students' understanding of complex scientific concepts related to energy, focusing on energy types, transformations, and the conservation law. The GIL model, characterized by active learning, student-centered inquiry, and structured guidance, was implemented through hands-on experiments, observations, and collaborative discussions. The results of the study revealed a significant improvement in scientific literacy, with a 25% increase in post-test scores. The findings suggest that GIL fosters greater student engagement and critical thinking compared to traditional lecture-based methods. Students demonstrated increased confidence and a deeper understanding of energy concepts, making connections between theoretical knowledge and real-world applications. Despite challenges such as time constraints and resource limitations, these obstacles were addressed by adjusting schedules and incorporating virtual simulations to enhance the learning experience. Student feedback was overwhelmingly positive, with participants expressing appreciation for the hands-on nature of the model and the opportunities for peer learning. This study underscores the effectiveness of GIL in improving scientific literacy and suggests that its application could extend to other scientific topics, providing a flexible framework for fostering inquiry and understanding in various educational contexts. Future research is recommended to explore the long-term impact of GIL on other science disciplines and evaluate its broader applicability across different educational settings.